Peran Pondok Pesantren dalam Menumbuhkan Jiwa Entrepreneur Santri - Fitrianingsih, Fitrianingsih; Shobirin, Mochammad Syafiuddin (LAN TABUR : Jurnal Ekonomi Syariah, 2023)
Islamic boarding schools are educational institutions that have long developed in Indonesia, Islamic boarding schools include elements that play a role in the spread of Islam in the form of education. The essence of Islamic boarding schools is the preparation of a generation to live their best life before Allah SWT, fulfilling their duties as caliphs on earth. However, according to the demands of the times, Islamic boarding schools must be able to produce graduates with various skills, because not all alumni become scholars or kiai. The purpose of this research is to gain a deeper understanding of how Islamic boarding schools play a role in fostering an entrepreneurial spirit among students at the Rahmatan Lil Alamin Islamic Boarding School. Entrepreneurship is a type of education given to the students of the Rahmatan Lil Alamin Islamic Boarding School as preparation for the future. Gaining entrepreneurial experience while in Islamic boarding schools can be one of the factors that helps graduates find job opportunities that generate financial benefits. This can be used as a shortcut to achieve higher income. The methods used in collecting data were interviews and document studies while the data analysis technique used a descriptive-qualitative approach.